High resolution X-ray photoemission study of nitrogen doped TiO2 rutile single crystals - Takahashi, I; Payne, D; Palgrave, R; Egdell, R (2008)
The electronic structure of nitrogen doped TiO2 prepared by annealing single crystal rutile (1 1 0) substrates in NH3 at elevated temperatures was investigated using high resolution X-ray photoelectron spectroscopy. NH3 treatment at 600 °C introduced N into the TiO2 lattice without concomitant surface reduction of the rutile phase. This doping leads to bandgap narrowing associated with the appearance of new N 2p electronic states above the O 2p band in valence region photoemission spectra. Surface modification at the higher temperature of 700 °C also produced bandgap narrowing but at the same time led to pronounced surface reduction. © 2008 Elsevier B.V. All rights reserved.